Laparoscopic Sentinel Lymph Node Biopsy for Prostate Cancer: The Relevance of Locations Outside the Extended Dissection Area. (19th September 2011) - Meinhardt, W.; van der Poel, H. G.; Valdés Olmos, R. A.; Bex, A.; Brouwer, O. R.; Horenblas, S.
Abstract : Objective . To assess the relevance of sentinel lymph nodes (SNs) outside the extended pelvic lymph node dissection area (e-PLND). Patients and Methods . Evaluation of our laparoscopic SN procedures for prostate cancer patients of intermediate prognosis. Retrospective data collection on the exact location of the excised SNs and the pathology results were analyzed. Results and Limitations . Of the 121 patients, 49 had positive lymph nodes. 37 patients (31%) had SNs outside the e-PLND template. Five of these nodes were tumor bearing but only twice exclusively so. Of the 14 patients considered for salvage treatment, 6 were node positive. 7 of these 14 patients (50%) had SNs outside the extended dissection area, yet none of these nodes were tumor positive. Limitations are those of a retrospective study. Conclusions . Laparoscopic SN biopsy may show SNs outside the e-PLND template in 31% of the patients. However, nodes that are exclusively positive in one of these areas are rare. For the dichotomy positive or negative nodes, the locations outside the e-PLND area are not often relevant. Nevertheless, when all positive nodes are to be treated by resection or radiotherapy, these locations are relevant. When considering salvage treatment for prostate cancer, the method is feasible.